PERAN PEMBELAJARAN TOEFL DALAM MENINGKATKAN KEMAMPUAN BAHASA INGGRIS MAHASISWA DI ERA DIGITAL - Muliasari, Dewi; Efendi, Tino Feri (JURNAL ILMIAH EDUNOMIKA, 2024)
This research explores the role of TOEFL (Test of English as a Foreign Language) learning in improving English proficiency among students in the Informatics program at AAS Indonesia Business Technology Institute in the digital era. The study investigates how the integration of technology in TOEFL preparation enhances language skills, particularly in listening, speaking, reading, and writing. Using a mixed-methods approach, the research includes surveys and interviews to gather data from students who have participated in TOEFL preparation programs incorporating digital platforms. The results indicate that technology-assisted TOEFL learning significantly boosts students' English proficiency, providing flexible access to materials and immediate feedback. However, challenges such as limited internet access, difficulties in self-motivation, and reduced interaction with instructors were identified as obstacles. The study suggests that while digital tools are highly effective, addressing these challenges will further optimize TOEFL learning outcomes. The research concludes that integrating technology into TOEFL preparation offers substantial benefits but requires careful consideration of the challenges involved.Â Keywords :TOEFL learning, digital learning, English proficiency, technology in education, online learning, Informatics students, AAS Indonesia Business Technology Institute, language skills improvement.